CircRNA and miRNA expression analysis in livers of mice with Toxoplasma gondii infection - Zou, Yang; Meng, Jin-Xin; Wei, Xin-Yu; Gu, Xiao-Yi; Chen, Chao; Geng, Hong-Li; Yang, Li-Hua; Zhang, Xiao-Xuan; Cao, Hong-Wei (Frontiers in Cellular and Infection Microbiology, 2022)
Toxoplasmosis is an important zoonotic parasitic disease caused by Toxoplasma gondii (T. gondii). However, the functions of circRNAs and miRNAs in response to T. gondii infection in the livers of mice at acute and chronic stages remain unknown. Here, high-throughput RNA sequencing was performed for detecting the expression of circRNAs and miRNAs in livers of mice infected with 20 T. gondii cysts at the acute and chronic stages, in order to understand the potential molecular mechanisms underlying hepatic toxoplasmosis. Overall, 265 and 97 differentially expressed (DE) circRNAs were found in livers at the acute and chronic infection stages in comparison with controls, respectively. In addition, 171 and 77 DE miRNAs were found in livers at the acute and chronic infection stages, respectively. Functional annotation showed that some immunity-related Gene ontology terms, such as “positive regulation of cytokine production”, “regulation of T cell activation”, and “immune receptor activity”, were enriched at the two infection stages. Moreover, the pathways “Valine, leucine, and isoleucine degradation”, “Fatty acid metabolism”, and “Glycine, serine, and threonine metabolism” were involved in liver disease. Remarkably, DE circRNA 6:124519352|124575359 was significantly correlated with DE miRNAs mmu-miR-146a-5p and mmu-miR-150-5p in the network that was associated with liver immunity and pathogenesis of disease. This study revealed that the expression profiling of circRNAs in the livers was changed after T. gondii infection, and improved our understanding of the transcriptomic landscape of hepatic toxoplasmosis in mice.